2018
DOI: 10.1016/j.cej.2018.02.061
|View full text |Cite
|
Sign up to set email alerts
|

Improving the functionality and performance of AA2024 corrosion sensing coatings with nanocontainers

Abstract: The compatibility between nanocontainers and coating formulations is perhaps the last frontier in the quest for functional coatings. Sensing coatings for early metallic corrosion detection is an urgently needed technology by aeronautical companies to mitigate the costs of corrosion through continuous monitoring. In this work, we revisit phenolphthalein encapsulated silica nanocapsules, which were incorporated into a water-based lacquer, resulting in a novel corrosion sensing coating for aluminum alloy 2024 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 39 publications
2
29
0
1
Order By: Relevance
“…Therefore, PNL molecule can be used as sensor for detecting early stage of corrosion. [ 37–40 ] Solutions of PVF with various amounts of PNL ( Table 1 ) were electrospun on steel substrates. Afterward, the obtained substrates were further covered by spin‐coating with P(MMA‐ co ‐BA) solutions with two different concentrations ( Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, PNL molecule can be used as sensor for detecting early stage of corrosion. [ 37–40 ] Solutions of PVF with various amounts of PNL ( Table 1 ) were electrospun on steel substrates. Afterward, the obtained substrates were further covered by spin‐coating with P(MMA‐ co ‐BA) solutions with two different concentrations ( Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…An alternative solution to achieve a good dispersion of the NCs into the PU matrix is to use the containers as powders and add them into the formulation the same way as pigments. This is done either using specific tools such as extruders or ball mills or simpler mechanical or magnetic stirring, potentially assisted with ultrasonication . Shi et al reported the presence of silicon‐richer areas within the epoxy resin they used even after a 30 min mixing step.…”
Section: Resultsmentioning
confidence: 99%
“…Recent developments showed very good results and enhancement of the release control using layered double hydroxides, zeolites, hollow fibers, particles, capsules or more unusual ones such as algae exoskeletons . Each one of these systems has shown protective properties when filled with inhibitors, despite sometimes a decrease in passive protection .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Frankel and Zhang used organic pH indicators such as phenolphthalein or coumarin to detect corrosion at the surface of an Al alloy . In spite of the direct addition of pH indicator being a simple route to impart corrosion detection ability to a protective coating, investigation in the field of anti‐corrosion coatings in the last 20 years has shown that often the direct addition of active compounds to coating formulations leads to unwanted reactions between the added compounds and other coating components, contributing to coating deterioration and/or loss of efficiency of the additive . To overcome this challenge, the concept of nanocontainers, inert structures with ability to store and release active compounds in a controlled way when local conditions are verified, was introduced.…”
Section: Introductionmentioning
confidence: 99%
“…For the purposes of corrosion sensing, Li and Calle, as well as Maia et al used polymeric particles to control the release of pH indicators and, at the same time, enhance the compatibility of the additive with the coating , . In other works by Tedim and colleagues, mesoporous silica particles loaded with the pH indicators were used instead , . In all the reported works, indication was achieved by color changes due to local alkalinization near the surface as a result of the cathodic half‐reaction of the corrosion process (Figure a).…”
Section: Introductionmentioning
confidence: 99%